Poverty and Wealth from the Perspective of Selected Psychological Concepts of Value - Kuświk, Justyna (Studia Historiae Oeconomicae, 2014)
The purpose of the paper is to discuss the issues associated with the psychological aspect of possessions. The basic question of our consideration refers to the place which poverty and wealth occupy among human values. In particular, the analysis of this article includes recognition of Milton Rokeach and Shalom H. Schwartz.